Audit Of Peri-Operative Care As Part Of The Enhanced Recovery Model For Caesarean Delivery - Blumenthal, Abigail (Department of Obstetrics and Gynaecology, 2023)
Introduction Mowbray Maternity Hospital (MMH) is a secondary level hospital serving a large population with low socioeconomic status. Around 10000 deliveries are done per year of which 40-50% are delivered by caesarean section (CS). There is much literature on peri-operative care for caesarean sections, under the model of fast-track surgery also known as Enhanced Recovery After Surgery (ERAS). ERAS protocols have antenatal, intra-operative and post-operative components. This audit aimed to evaluate how successfully MMH adheres to local and international guidelines for peri-operative care around elective caesarean section according to the ERAS model. It is hoped this will form the first step in a quality-improvement intervention resulting in better quality, evidence-based care appropriate for the low-resource setting. Materials & Methods: Women were invited to participate in the study in MMH postnatal ward between 24 and 48 hours after elective CS. Once consented, a structured questionnaire and data collection sheet was used to interview women and remaining details were obtained from the patient record. This covered four aspects of ERAS programmes: 1. peri-operative hydration and nutrition 2. peri-operative analgesia 3. time interval postoperatively until removal of intravenous lines and urinary catheterisation 4. time interval until first mobilisation The initial planned sample size was 50 women however after the start of the covid pandemic when in-person interviews were no longer possible, a folder audit was undertaken of the remaining files. A decision was made to therefore increase the sample size to increase the value of the data obtained from the folder audit given that there was to be more limited data from patient interviews. Anonymised data was entered into a secure online database using REDCap (Research Electronic Data Capture system). Data entry was verified by double entering all data. In total 75 folders were reviewed, of which 35% were interviewed face-to-face. Findings The audit showed that 92% of patients received exactly the same number of doses (four 10mg doses) of morphine post-operatively with more variation in the dosing of simple oral analgesics and no use of NSAIDs. It showed that 85% of patients had high pain scores (3 or more out of 5) in the first 24 hours post caesarean section but 85% also reported they were mildly or very happy with their pain management post-operatively. The audit highlighted that many patients were nilper-os for prolonged periods of time peri-operatively; on average 23 hours without food and 19 hours without oral fluid. Drips and catheters were removed on average at 12.5 hours post- operatively; and mobilisation occurred on average at 12 hours with few delays; the standard deviation was less than 1 hour. Conclusions The audit confirmed that Mowbray Maternity Hospital has good adherence to certain ERAS protocols. It confirmed that most patients were happy with their pain control despite often reporting high levels of pain. However, it highlighted several deficiencies such as poor use of regular simple oral analgesia and the lengthy duration of time for which many patients were fasted which could impact on general satisfaction with care, not to mention possible negative effects on tissue healing.